Training Needs of Grass-Root Level Extension Worker - Kumari Kavita , Dibyanshu Shekhar and A. K. Singh (Indian Journal of Extension Education, 2017)
The multiplicity of extension systems are under operation in India considering the varied agro-ecological situations underwhich farmers reside, besides variations in the resource base of farmers. The extension system envisaged to achievedesired growth in agricultural sector with pluralistic in nature. Visualizing the need to deploy trained man power at grassroot level for ensuring effective extension, the Government of Bihar state appointed Agriculture Coordinator and KisanSalahkar at panchayat level to cater the farmers' information need and to assist the farmers for giving them advantages ofongoing agricultural developmental programmes. Training needs for grass root level extension personnel can be definedin terms of gap between job requirement and job performance. During the study the training need was assessed in thethematic areas like improved agricultural practices, organization and administration, programme development andexecution, communication skill and social system and local leadership with the help of Agriculture Coordinator and KisanSalahkar as the sample. The results of the study reveal that perceived training about improved agricultural technology wasvery much needed by the 73.33 per cent of the Agriculture Coordinator, whereas 87.79 per cent of Kisan Salahkar werealso showed the same pattern of this responses